2021
DOI: 10.3390/fluids6110407
|View full text |Cite
|
Sign up to set email alerts
|

An Arbitrary Hybrid Turbulence Modeling Approach for Efficient and Accurate Automotive Aerodynamic Analysis and Design Optimization

Abstract: The demand in solving complex turbulent fluid flows has been growing rapidly in the automotive industry for the last decade as engineers strive to design better vehicles to improve drag coefficients, noise levels and drivability. This paper presents the implementation of an arbitrary hybrid turbulence modeling (AHTM) approach in OpenFOAM for the efficient simulation of common automotive aerodynamics with unsteady turbulent separated flows such as the Kelvin–Helmholtz effect, which can also be used as an effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…This computational study is performed using adapted Large Eddy Simulations with a particular emphasis on the signal type influence. Large Eddy Simulations are still considered as the most accurate computational approaches to simulate and control turbulent flows around such geometries [25,26]. The numerical method for the base flow is initially validated comparing to in house experiments before being generalized to controlled cases.…”
Section: Introductionmentioning
confidence: 99%
“…This computational study is performed using adapted Large Eddy Simulations with a particular emphasis on the signal type influence. Large Eddy Simulations are still considered as the most accurate computational approaches to simulate and control turbulent flows around such geometries [25,26]. The numerical method for the base flow is initially validated comparing to in house experiments before being generalized to controlled cases.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, it appears that the high drag coefficient moment is always caused by the production of a more complicated or strong vortex motion. An Arbitrary Hybrid Turbulence Modeling (AHTM) was developed by Maulenkul et al [17] using a combination of Reynolds Averaged Navier-Stokes (RANS), Unsteady Reynolds Averaged Navier-Stokes (URANS), Large Eddy Simulation (LES), and Direct Numerical Simulation (DNS) turbulence models in a single flow field based on the local mesh refinement. When compared to the traditional benchmark case of an Ahmed body, their findings indicated that the ATHM is the most precise of all turbulent models.…”
Section: Introductionmentioning
confidence: 99%